2012
DOI: 10.1002/jcp.23022
|View full text |Cite
|
Sign up to set email alerts
|

Telocyte morphologies and potential roles in diseases

Abstract: Telocytes (TCs) are a new type of interstitial cells, a small cellular body with the presence of 2-5 prolongations named as telopode (Tp)-very thin (less than 0.2 µm) and extremely long (10-1,000 µm), a moniliform aspect, and caveolae, containing a nucleus surrounded by a small amount of cytoplasm. The nucleus occupies about 25% of TC body volume and contains clusters of heterochromatin attached to the nuclear envelope. The perinuclear cytoplasm is rich in mitochondria and contains a small Golgi complex, rough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 57 publications
3
86
0
7
Order By: Relevance
“…and Zheng et al, [2012] suggested that telocytes are located near vessels; they might be involved in blood flow regulation. observed telocyte contacts with nerve fibers and/ or smooth muscle cells in the human uterine tube.…”
Section: Discussionmentioning
confidence: 99%
“…and Zheng et al, [2012] suggested that telocytes are located near vessels; they might be involved in blood flow regulation. observed telocyte contacts with nerve fibers and/ or smooth muscle cells in the human uterine tube.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, potential relationships between telocytes and other cells in lung diseases are proposed and summarized by Zheng et al [42]. Telocytes may be a new target cell for the prevention and treatment of lung diseases, although there is still a need for further studies on the details of their biological functions during the pathologic status of the lung.…”
Section: Zheng Bai and Wangmentioning
confidence: 99%
“…The phenotype of TCs was characterized by CD34, c-kit, vimentin and caveolin-1 positivity [21]. TCs in different tissues display different phenotypes [22,23]. Cardiac TCs express vimentin, CD34 and PDGFR-β [16].…”
Section: Introductionmentioning
confidence: 99%